Pengaruh Return on Assets dan Net Profit Margin terhadap Harga Saham Perbankan - Achmad Wahyudi; Mappamiring Parenta; Dwi Anuggerah Lestari Musa; Herman Sjahruddin (BISMA : Business and Management Journal, 2026)
The movement of bank stock prices indicates the level of investor confidence in political stability, legal certainty, and the potential economic growth of a country. This serves as the fundamental argument for why it is highly important to research the factors influencing banking stock prices, such as Return on Assets (ROA) and Net Profit Margin (NPM). This study aims to analyse the effect of ROA and NPM on the stock prices of banking sub-sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The banking sector was selected on the grounds that banking plays a crucial role in maintaining national economic stability and constitutes one of the sectors highly sought after by investors.  This research adopts a quantitative approach using the panel data regression analysis method. The research data were obtained from the annual financial statements of banking companies published via the official website of the Indonesia Stock Exchange. The research population consisted of 30 listed issuers, with a sample of 25 companies selected using a purposive sampling technique. The results of the study indicate that a high Return on Assets is proven to increase banking stock prices. On the other hand, it is demonstrated that a high Net Profit Margin in its implementation fails to increase banking stock prices